Multinuclei Occurred Under Cryopreservation and Enhanced the Pathogenicity of Melampsora larici-populina - Zheng, Wei; Peng, Zijia; Peng, Shaobing; Yu, Zhongdong; Cao, Zhimin (Frontiers in Microbiology, 2021)
Melampsora larici-populina is a macrocyclic rust, and the haploid stage with two nuclei and the diploid of mononuclear sequentially occur annually. During the preservation of dry urediniospores at −80°C, we found that one isolate, ΔTs06, was different from the usual wild-type isolate Ts06 at −20°C because it has mixed polykaryotic urediniospores. However, the other spores, including the 0, I, III, and IV stages of a life cycle, were the same as Ts06. After five generations of successive inoculation and harvest of urediniospores from the compatible host Populus purdomii, the isolate ΔTs06 steadily maintained more than 20% multiple nucleus spores. To test the pathogenesis variation of ΔTs06, an assay of host poplars was applied to evaluate the differences between ΔTs06 and Ts06. After ΔTs06 and Ts06 inoculation, leaves of P. purdomii were used to detect the expression of small secreted proteins (SSPs) and fungal biomasses using quantitative real-time PCR (qRT-PCR) and trypan blue staining. ΔTs06 displayed stronger expression of five SSPs and had a shorter latent period, a higher density of uredinia, and higher DNA mass. A transcriptomic comparison between ΔTs06 and Ts06 revealed that 3,224 were differentially expressed genes (DEGs), 55 of which were related to reactive oxygen species metabolism, the Mitogen-activated protein kinase (MAPK) signaling pathway, and the meiosis pathway. Ten genes in the mitotic and meiotic pathways and another two genes associated with the “response to DNA damage stimulus” all had an upward expression, which were detected by qRT-PCR in ΔTs06 during cryopreservation. Gas chromatography–mass spectrometry (GC-MS) confirmed that the amounts of hexadecanoic acid and octadecadienoic acid were much more in ΔTs06 than in Ts06. In addition, using spectrophotometry, hydrogen peroxide (H2O2) was also present in greater quantities in ΔTs06 compared with those found in Ts06. Increased fatty acids metabolism could prevent damage to urediniospores in super-low temperatures, but oxidant species that involved H2O2 may destroy tube proteins of mitosis and meiosis, which could cause abnormal nuclear division and lead to multinucleation, which has a different genotype. Therefore, the multinuclear isolate is different from the wild-type isolate in terms of phenotype and genotype; this multinucleation phenomenon in urediniospores improves the pathogenesis and environmental fitness of M. larici-populina.